An ambulance referral network improves access to emergency obstetric and neonatal care in a district of rural Burundi with high maternal mortality. Issue 8 (18th May 2013) - Tayler‐Smith, K.; Zachariah, R.; Manzi, M.; Van den, W.; Nyandwi, G.; Reid, T.; De, E.; Lambert, V.; Nicolai, M.; Goetghebuer, S.; Christiaens, B.; Ndelema, B.; et al.
Abstract Objectives In 2006, Médecins sans Frontières (MSF) established an emergency obstetric and neonatal care (EmONC) referral facility linked to an ambulance referral system for the transfer of women with obstetric complications from peripheral maternity units in Kabezi district, rural Burundi. This study aimed to (i) describe the communication and ambulance service together with the cost; (ii) examine the association between referral times and maternal and early neonatal deaths; and (iii) assess the impact of the referral service on coverage of complicated obstetric cases and caesarean sections. Methods Data were collected for the period January to December 2011, using ambulance log books, patient registers and logistics records. Results In 2011, there were 1478 ambulance call‐outs. The median referral time (time from maternity calling for an ambulance to the time the patient arrived at the MSF referral facility) was 78 min (interquartile range, 52–130 min). The total annual cost of the referral system (comprising 1.6 ambulances linked with nine maternity units) was € 85 586 (€ 61/obstetric case transferred or € 0.43/capita/year). Referral times exceeding 3 h were associated with a significantly higher risk of early neonatal deaths (OR, 1.9; 95% CI, 1.1–3.2). MSF coverage of complicated obstetric cases and caesarean sections was estimated to be 80% and 92%, respectively. Conclusion This study demonstrates that it is possible to implement an effective communication and transport system to ensure access to EmONC and also highlights some of the important operational factors to consider, particularly in relation to minimising referral delays.